There is hope and help: Reach and reception of a methamphetamine education campaign in Los Angeles County, California - Carolyn A. Stalgaitis; Jeffrey W. Jordan; Brandon Tate; Brian Cruse; Michelle Bellon; Rangell Oruga; Brian Hurley (Preventive Medicine Reports, 2023)
Introduction: In the context of increasing rates of methamphetamine (meth) overdose in Los Angeles County, California, USA, in 2021 the Los Angeles County Department of Public Health relaunched Meth Free LA County, a methamphetamine public education campaign built on Rescue Agency’s Decision BlocksTM Strategic Framework. Methods: To assess campaign reach and reception, we examined media data and an online cross-sectional post-campaign survey in 2021 with a convenience sample of 750 county residents ages 18–54 who had used meth, were at-risk, or had personal relationships with people at-risk. We assessed campaign awareness, receptivity, and perceived effectiveness. Participants also reported concern about meth use in their community, recall of 10 facts from campaign content, and if they had taken promoted actions such as seeking help. We compared proportions between campaign-aware and unaware participants and explored if recall predicted these measures. Results: Most participants recalled the campaign (84.1%), felt it offered a new way of looking at meth (73.8%), and reported it made them feel that help is available (84.0%) or that it could help reduce their own use (82.4%). Video advertisements received high perceived effectiveness scores. Greater campaign recall was associated with significantly increased odds of being concerned about meth use in the community, recalling facts, and taking promoted actions. Conclusion: In 2021, Meth Free LA County reached its high-risk audiences. Unlike fear-based campaigns its message resonated with high-risk individuals, providing an example of how public education campaigns on meth and similar illicit substances can connect with their audiences.